Rethinking Climate Diplomacy Gains: Strategic Benefits to Nepal - Pandey, Chandra Lal; Dahal, Ngamindra (Journal of Foreign Affairs, 2022)
Nepal is one of the most vulnerable countries in the world when it comes to climate change, which has become a major threat to development and in building disaster-resilient urban and rural communities. The Intergovernmental Panel on Climate Change (IPCC) sixth assessment report of 2021 termed the climate crisis as “Code Red”, signifying that climate change is already causing substantial physical, environmental, social, and economic losses, and damages in both developing and developed countries. The impacts of climate change are disproportionate for countries like Nepal, which must bear the brunt of the impacts even though their contribution to making global warming is minimal. However, the politics of developed and the developing countries and changing economic realities of many influential nations complicate multilateral, bilateral, trilateral and regional climate negotiations. Most recent scientific reports suggest that if countries do not take decisive action to reduce greenhouse gas emissions now, the world is going beyond the 2°C rise limit soon and will affect, inter alia, the mountain ecosystem, freshwater system, agriculture, livelihood, and development practices. The impacts of climate change are increasing rapidly in various sectors of Nepali human and natural ecosystems. Therefore, addressing the impacts of it is paramount, and requires mitigation and adaptation measures, which includes efficacious climate diplomacy. Qualitative assessments indicate that Nepal needs to adopt a new approach to climate diplomacy to ethically encourage big economies and the rest of the world to go beyond conventional binary options of relations between the developed and developing countries. Adaptation and mitigation are the best available approaches to addressing climate change vulnerabilities and building resilient communities. Therefore, an interdisciplinary negotiation team would be needed in the diplomatic efforts to articulate priorities and evidence-based impacts and for tapping the international resources – state-of-art-knowledge, finances, and technologies – to assist the country to fight against climate threats.